Aspectos da industrialização da castanha de caju (Anacardium accidentale, L.) - Andrade, Jerusa de Souza (1984)
The cashew nut kernels (Anacardium occidentale, L.) used in this work were obtained from Caju do Brasil S.A Agro Industrial - CAJUBRAZ, a plant located in Pacajus - Ceará - Brazil. They were selected out of several stages of processing, such as: cracking/separation, shelling, storage before and after roasting. [...]